The implementation of effective communication principles in the tuberculosis cadre re-training activity - Santoso, Windu; Sudarsih, Sri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Effective communication is one of the abilities that must be possessed by TB cadres (tuberculosis) in carrying out their duties. This ability must always be honed so that we need a form of re-training to improve communication skills in providing counseling and training in the community. This research aims to measure the effective communication skills of TB cadres (tuberculosis) in the Re-Training Activity which is carried out for 4 days. The method used in this research is descriptive. Retrieval of data with an observation sheet in the form of a checklist designed according to seven components in effective communication. The population was all TB cadres who participated in the Re training and a sample of 27 cadres. The results showed 59.3 percent had effective communication skills. Based on the criteria of effective communication on the criteria of the suitability of messages with the needs of respondents, the use of communion channels, empathy is above 81.5 percent, while the components of message clarity, completeness of planning and organizing messages, feedback and understanding of messages as well as the contents of messages delivered on average still not enough. The results of this research are very useful as a basis for determining the follow up of cadre re training so that cadres will be more trustworthy and able to improve their abilities in carrying out their duties. ABSTRAKKomunikasi Efektif merupakan salah satu kemampuan yang harus dimiliki oleh kader TB (tuberkulosis) dalam melaksanakan tugas. Kemampuan ini harus selalu terasah sehingga diperlukan sebuah bentuk re-training untuk meningkatkan kemampuan komunikasi dalam memberikan penyuluhan dan pelatihan dimasyarakat. Penelitian ini bertujuan untuk mengukur kemampuan komunikasi efektif pada kader TB (tuberkulosis) dalam Kegiatan Re-Training yang dilaksanakan selama 4 hari. Metode yang digunakan dalam penelitian ini deskriptif. Pengambilan data dengan lembar observasi berupa ceklis yang di rancang sesuai tujuh komponen dalam komunikasi efektif. Populasi adalah seluruh kader TB yang mengikuti Re training dan sampel sebesar 27 orang kader. Hasil penelitian menunjukkan 59,3 persen memiliki kemampuan komunikasi efektif. Berdasarkan kritria komunikasi efektif pada kriteria kesesuaian pesan dengan kebutuhan responden, penggunaan saluran komuni, sikap empati di atas 81,5 persen, sedangkan pada komponen kejelasan pesan, kelengkapan perencanaan dan pengorganisasian pesan, umpan balik dan pemahaman pesan serta isi pesan yang disampaikan rata-rata masih kurang. Hasil penelitian ini sangat bermanfaat sebagai dasar dalam menentukan tindak lanjut re training kader sehingga kader akan lebih percaya dari dan mampu meningkatkan kemampuan dalam menjalankan tugasnya.